Neural Activity Predicts Reaction in Primates Long Before a Behavioral Response - Parto Dezfouli, Mohsen; Khamechian, Mohammad Bagher; Treue, Stefan; Esghaei, Moein; Daliri, Mohammad Reza (Frontiers in Behavioral Neuroscience, 2018)
How neural activity is linked to behavior is a critical question in neural engineering and cognitive neurosciences. It is crucial to predict behavior as early as possible, to plan a machine response in online brain computer interactions. However, previous studies have studied the neural readout of behavior only within a short time before it is performed. This leaves unclear, if the neural activity long before a decision could predict the upcoming behavior. By recording extracellular neural activities from the visual cortex of behaving rhesus monkeys, we show that 1) both, local field potentials (LFP) and the rate of neural spikes long before (>2 sec) a monkey detects a change, foretell its behavioral performance in a spatially selective manner. 2) the more accessible component of the extracellular activity, LFP is a stronger predictor of behavior. 3) LFP amplitude is positively correlated and spiking activity is negatively correlated with behavioral reaction time. These results suggest that field potentials could be used to predict behavior very early before it is performed, especially useful for brain computer interface applications and that they are importantly linked to the sensory neural circuit’s speed in information processing.